Optical nets brace for even heavier traffic. - Riezenman, M.J (IEEE spectrum)
Thanks to that Internet, backbone traffic has been increasing at a compound annual growth rate of more than 100 percent for several years. The owners of the backbone infrastructure, which is almost entirely fiber-based, are therefore eagerly embracing technologies that add to the capacity of fiber-optic systems without adding mountains of new optical cable. Having sufficient backbone capacity doesn't mean that everyone gets a high-speed connection to the Internet. It simply means that huge quantities of data can be transported between and among certain locations. There is still the problem of the last mile-the connection between the service provider and the end-user. The economics of using fibre for the last mile are open to question. One alternative approach to the last mile is fiberless optics-transmitting unguided laser beams through the air. Yet to be commercially deployed, the technology promises both high transmission speeds and fast provisioning (installation). The author describes this technology as well as ways to increase the capacity of optical fibres using WDM or raising the bit rate of each TDM data stream